Hubungan antara pendekatan belajar dan prestasi akademik pada sistem pembelajaran "problem based learning" - Farida Juliantina Rachmawaty, Isnatin Miladiyah dan Shofyatul Yumna Triyana (Berita Kedokteran Masyarakat (BKM), 2005)
Background: Recently Problem-based Learning (PBL) in higher education is highlighted, especially in the medical education. PIK is considered as a better alternative. This method encourages students to be self-directed learners and having learning skills to become lifelong learners. A doctor must base their acts on the highest performances, thus lifelong learning is needed. Objective: This study were aimed at examining learning approaches of students of Faculty of Medicine, Islamic University of Indonesia and to approve the relationship between learnig approaches and academic achievement in PIK method. Methods: Subjects participating in this study were students of first level of Faculty of Medicine Islamic University of Indonesia, and this was a cross-sectional study. Learning approaches was obtained by questionnaire as primary data, and academic achievement used GPA as secondary data. Data were analyzed with SPSS 11 on computer programme using Spearman correlation and discriminating power test using Mann-Whitney test. Results: The results showed that Surface Approach had inverse correlation with academic achievement of students